Mild hemolytic anemia, progressive neuromotor retardation and fatal outcome: a disorder of glycolysis, triose- phosphate isomerase deficiency - Sarper, Nazan; Zengin, Emine; Jakobs, Cornelis; Salomons, Gajja S.; MC Wamelink, Mirjam; Ralser, Markus; Kurt, Koray; Kara, Bülent (The Turkish Journal of Pediatrics, 2013)
A two-month-old male infant presented with jaundice, pallor, and hepatomegaly. The first child of non-consanguineous parents had also suffered from hemolytic anemia and neuromotor retardation and died at the age of 21 months. The patient required phototherapy and transfusion in the newborn period but hemolysis was mild thereafter. The patient had neuromotor retardation, and at the age of 14 months, ventilatory support was necessary, and the patient lived until 17 months. Triose-phosphate isomerase (TPI) deficiency, which is a rare autosomal recessive multisystem disorder of glycolysis, was detected. There was homozygous missense mutation in the TPI1 gene (p.Glu105Asp). This is the most common mutation with a severe phenotype that requires ventilator support in the second year of life. In patients with hemolysis and neuromotor retardation, TPI deficiency must be considered. There is no specific treatment, but detection of the index case may provide the opportunity for genetic counseling and prenatal diagnosis.